On the Coderivative of the Projection Operator onto the Second-order Cone - Outrata, Jiří V.; Sun, Defeng (Set-valued analysis, 2008)
The limiting (Mordukhovich) coderivative of the metric projection onto the second-order cone is computed. This result is used to obtain a sufficient condition for the Aubin property of the solution map of a parameterized second-order cone complementarity problem and to derive necessary optimality conditions for a mathematical program with a second-order cone complementarity problem among the constraints.